2022
DOI: 10.3390/plants11050666
|View full text |Cite
|
Sign up to set email alerts
|

Vegetation Composition of the Halophytic Grass Aeluropus lagopoides Communities within Coastal and Inland Sabkhas of Saudi Arabia

Abstract: Sabkhas are unique, highly saline ecosystems, where specially adapted plants can grow. Aeluropus lagopoides (L.) Thwaites is a halophytic forage plant growing in salt marsh habitats of inland and coastal sabkhas of Saudi Arabia. The present study provides an analysis of vegetation composition and distribution of the A. lagopoides community in five different regions within Saudi Arabia, emphasizing the environmental factors that affect species distribution. The floristic survey revealed the presence of 48 speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Therefore, detecting the variations in plant species’ distributions for the purpose of providing a logical perception of the environmental requirements of the species needed for successful ecological restoration is important [ 24 ]. On the other hand, knowledge of the ecological distribution of key species is the primary characteristic of the conservation strategy for its ecosystem [ 25 , 26 ]. Therefore, this research aimed to determine the environmental factors important for the distribution of K. odoratissima in Iran using BMLR modeling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, detecting the variations in plant species’ distributions for the purpose of providing a logical perception of the environmental requirements of the species needed for successful ecological restoration is important [ 24 ]. On the other hand, knowledge of the ecological distribution of key species is the primary characteristic of the conservation strategy for its ecosystem [ 25 , 26 ]. Therefore, this research aimed to determine the environmental factors important for the distribution of K. odoratissima in Iran using BMLR modeling.…”
Section: Discussionmentioning
confidence: 99%
“…Following this factor, evaporation (beta= 8.282) and slope (beta = 0.807) had the next greatest effects, respectively. In this regard, previous studies reported that the most important factor affecting the distribution of Pomatosace filicula was predicted to be altitude [ 26 ]. Based on our results, K. odoratissima grows in heights of 2450 to 3000 m within the region of study.…”
Section: Discussionmentioning
confidence: 99%
“…Along the coastal regions, it is common to find great variations in species richness (number of annuals and perennials) among distinct habitats. This may be justified by the level of salinity, soil moisture and structure, topography and human impacts [ 16 , 17 , 56 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with saline environments, soil salinity is the main ecological feature that affects vegetation composition [ 3 , 59 , 60 , 61 , 62 ]. In addition, several studies highlighted the importance of soil texture, fertility and pH in controlling vegetation composition and patterns [ 16 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation